Mrs. Frisby and the rats of Nimh - O'Brien, Robert C.; Bernstein, Zena (New York : Aladdin Books, 1986)
Having no one to help her with her problems, a widowed mouse visits the rats whose former imprisonment in a laboratory made them wise and long lived.
Mrs. Frisby, a widowed mouse with four small children, is faced with a terrible problem. She must move her family to their summer quarters immediately, or face almost certain death. But her youngest son, Timothy, lies ill with pneumonia and must not be moved. Fortunately, she encounters the rats of NIMH, an extraordinary breed of highly intelligent creatures, who come up with a brilliant solution to her dilemma. And Mrs. Frisby in turn renders them a great service.
Keywords: Mice -- Fiction; Rats -- Fiction